Development of Interactive Learning Application for Basic Programming Based on Technological Pedagogical Content Knowledge Framework - Daniel Yulius Soetjipto; Hendra Dinata; Melissa Angga; Jovan Adriel Widjaja (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
Information technology students must take Algorithms and Programming. Research shows that 28% of US students fail their basic programming subject, which is essential to mastering programming. In line with the previous study, 39% of students in the Informatics Engineering department’s basic programming course at campus X in the odd semester of 2022/2023 failed the course. The learning process should be able to integrate technology into it. An interactive learning application was developed utilizing the Technological Pedagogical and Content Knowledge (TPACK) framework, incorporating a pedagogical paradigm in its design through simulation elements and animated visuals. Through an extensive design, this learning application enhances student engagement by 78.3%, encouraging continued utilization in their educational process. The trial involving the group of students utilizing this application revealed that 5 out of 34 students failed the course, in contrast to 7 out of 33 students from the group that studied without the application.